1988
DOI: 10.1136/bmj.297.6656.1083
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of geriatric rehabilitative care after fractures of the proximal femur in elderly women: a randomised clinical trial.

Abstract: Objective-To compare postoperative collaborative care between orthopaedic surgeons and physicians in geriatric medicine with routine orthopaedic care in elderly women with proximal femoral fracture.Design-Exclusion of patients dying before fit enough to enter trial, those with pathological fractures, those likely to be discharged within seven days of entering the trial, and those remaining unfit for transfer to a peripheral hospital. Remainder allocated to two groups: treatment group and control group.Setting-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
1
3

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 23 publications
3
108
1
3
Order By: Relevance
“…Similar models of comanaged care, including the geriatric fracture center described by Friedman et al [5,6] and the comprehensive geriatric intervention described by Vidán et al [21], are focused on protocol-driven care and quality management. The outcomes in our analysis of inpatient complications in male patients before and after implementation of the MOTS program replicate results most recently described in the United States [5,6], Australia [4], and Spain [21] but also the experiences described previously in the United Kingdom [7,12] (Table 3). As suggested by Vidán et al [21], it is likely the lower likelihood of experiencing at least one postoperative complication is due to early identification of high-risk patients through early and regular involvement of internists, as their more specialized training allows them to identify and properly treat medical problems.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar models of comanaged care, including the geriatric fracture center described by Friedman et al [5,6] and the comprehensive geriatric intervention described by Vidán et al [21], are focused on protocol-driven care and quality management. The outcomes in our analysis of inpatient complications in male patients before and after implementation of the MOTS program replicate results most recently described in the United States [5,6], Australia [4], and Spain [21] but also the experiences described previously in the United Kingdom [7,12] (Table 3). As suggested by Vidán et al [21], it is likely the lower likelihood of experiencing at least one postoperative complication is due to early identification of high-risk patients through early and regular involvement of internists, as their more specialized training allows them to identify and properly treat medical problems.…”
Section: Discussionsupporting
confidence: 85%
“…Because of the retrospective nature of the study and its limit to a review of inpatient documentation, we were unable to evaluate for the functional impact of the MOTS program at further postdischarge time points. Vidán et al [21] have shown an improvement in recovery of previous activities and function at 3 months postdischarge with a comprehensive geriatric hip fracture intervention but were unable to show maintenance of this improvement at 6 and 12 months postdischarge When viewed in the context of similar studies that did not show a difference in within-year mortality [7,12,13], our findings further support the possibility that focused multidisciplinary models of care may improve short-term outcomes for patients with hip fractures but may not yield longer-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The economic advantages gained by transferring postoperative rehabilitation to the geriatric department are thus largely a matter of accounting. Several studies show a shortened hospital stay when elderly hip fracture patients are treated in specialized geriatric rehabilitation units (Boyd et al 1983, Sainsbury et al 1986, Murphy et al 1987, Kennie et al 1988, Hempsall et al 1990, ZidCn et al 1990). The results, however, are usually compared with historic data and patient selection probably occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Orthopaedic and multidisciplinary geriatric teams within such services are dually responsible for provision of comprehensive collaborative pre-, peri-and post-operative care. Compared with usual (orthopaedic) care, orthogeriatric liaison services result in shorter hospital lengths of stay (up to 46% less), [20][21][22][23] greater functional independence with consequently higher rates of home discharge and lower nursing home placement (about 69% less), 20,21 and are cost effective (up to 16% reduction in costs per patient). 24 In contrast, inpatient geriatric consultation services providing management recommendations but without a mandate to implement these recommendations appear to have little impact on in-hospital complication rates, lengths of stay, mortality and subsequent re-admission rates.…”
Section: Geriatric Inpatient Consultation Servicesmentioning
confidence: 99%